A Method of Record Linkage - Oshima, Akira; Sakagami, Fumio; Hanai, Aya; Fujimoto, Isaburo (Environmental health perspectives, 1979)
In cancer epidemiology, prospective approaches are very important both in testing etiological hypotheses and in evaluating preventive procedures. Prospective studies, however, are very difficult and expensive, because a large number of people and a long period of observation are necessary for a satisfactory study. As a data source for follow-up studies, population-based cancer registry is very useful. The Osaka Cancer Registry has been in operation since December, 1962. Since 1968 the data processing, including the work of collation, has been semicomputerized. In order to identify cancer patients, we use the following six indices: date of birth, first Chinese character of a person's family name, address a: city, ward, town or village, address b: further details, i.e., street, avenue, section, hamlet etc., site, and sex. When we have data on the collation indices for the subjects to be followed up, we can conduct follow-up studies easily and accurately, using a semicomputerized collation method similar to that in the cancer registration system. Because the master file of the Osaka Cancer Registry contains the data of cancer cases reported and all cancer deaths among the residents of Osaka Prefecture, we can follow up the subjects living in Osaka Prefecture and obtain data about virtually all cancer incidences and deaths among them. In this follow-up method by means of record linkage to the cancer registry, some considerations should be taken into account for the following factors; coverage of cancer data in the Osaka Cancer Registry, reliability of the collation method, and address of the subjects to be followed up. As an example of a study with this method, we present the follow-up study of the screenees of a mass screening program for stomach cancer.